If you would like to simplify Q + S - T, you can do this using the following steps:
Q = 7m + 3n,
R = 11 - 2m,
S = n + 5,
T = -m - 3n + 8
Q + S - T = 7m + 3n + n + 5 - (-m - 3n + 8) = 7m + 3n + n + 5 + m + 3n - 8 = 8m + 7n - 3
The correct result would be 8m + 7n - 3.
Answer:
Step-by-step explanation:
let the 3rd side, the hypotenuse, be x
Using Pythagoras' identity in the right triangle.
The square on the hypotenuse is equal to the sum of the squares on the other 2 sides, that is
x² = 2² + 3² = 4 + 9 = 13 ( take square root of both sides )
x =
Answer:
Step-by-step explanation:
It is a right triangle and you have the measure of the cathets, we use the Pythagorean theorem
√(3² + 2²) =
√(9 + 4) =
√13
Answer:A=P+PRT
Step-by-step explanation:
Answer:
a76 = 8 + (76-1)*6
= 8 + 75*6
= 8 + 450
= 458
the 76th term of the arithmetic sequence 8, 14, 20 is 458
The equation of the line that passes through the points (2,1) and (6,-5) is y = -3/2x + 4. This is calculated using the formula for a line y - y1 = m(x - x1) and the formula for slope.
In order to find the equation of the line passing through the points (2,1) and (6,-5), we can use the formula for a line y - y1 = m(x - x1). Here, m is the slope of the line. We can calculate the slope using the formula (y2 - y1) / (x2 - x1). Thus, for the points (2,1) and (6,-5), the slope m is (-5 - 1) / (6 - 2) = -6/4 = -3/2. We can substitute one pair of points and the slope into the line equation. Let's use (2,1). The equation of this line is then y - 1 = -3/2 * (x - 2). Simplifying, we get the equation of the line to be y = -3/2x + 4.
#SPJ2